Constitutional interpretation: method and interpreter problems (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The constitutional rule, although does not seem to require a different interpretationof which is applied to the rest of the rules of the legal system, shows special featuresthat distinguished it. Thus it can be said that specificity that offers the interpretationof the constitutional rule isn’t method, but the object, and therefore bothbecause of its open nature, which translates into a greater presence in it of indeterminateconcepts, principles and values as per their legal character eminently political.In addition, this necessarily connects to debate about who should be the last interpreterof the constitutional text in the constitutional-political system. Both discussionsthat crosses itself general theory of the Constitution, debate of method anddebate of the interpreter, are closely interrelated, so that the method will be significantlyinfluenced by the subject and vice versa. If the constitutional norm has anopen and incomplete standard which would regulate Community adopts it for a longperiod of time (the relevant constitutional stability), the last interpreter must necessarilyhold a broad interpretation area. This wide margin precisely generates mistrust,either towards the Constitutional Court as a supreme organ of interpretation, eithertowards the Parliament as an expression directly in the will of the people.In short, the problems of interpretation and interpreter lead to the classic andunresolved dilemma between democracy and constitutionalism.
Keywords: constitutional hermeneutic; constitutional interpretation; Constitutional Court; counter-majoritarian power; majoritarian principle; override or notwithstanding clauses.